Molecular and Biological Characterization of a New Strawberry Cytorhabdovirus - Fránová, Jana; Přibylová, Jaroslava; Koloniuk, Igor (Viruses, 2019)
Virus diseases of strawberry present several complex problems. More than 25 viruses have been described in the genus Fragaria thus far. Here, we describe a novel rhabdovirus, tentatively named strawberry virus 1 (StrV-1), that infects F.ananassa and F.vesca plants. Genomic sequences of three distinct StrV-1 genotypes co-infecting a single F.ananassa host were obtained using combined Illumina and Ion Proton high-throughput sequencing. StrV-1 was transmitted to herbaceous plants via Aphisfabae and A.ruborum, further mechanically transmitted to Nicotianaoccidentalis 37B and sub-inoculated to N.benthamiana, N.benthamiana DCL2/4i, N.occidentalis 37B, and Physalisfloridana plants. Irregular chlorotic sectors on leaf blades and the multiplication of calyx leaves seem to be the diagnostic symptoms for StrV-1 on indexed F.vesca clones. StrV-1 was detected in asymptomatic grafted plants and in 49 out of 159 field strawberry samples via RT-PCR followed by Sanger sequencing. The bacilliform shape of the virions, which have a cytoplasm-limited distribution, their size, and phylogenetic relationships support the assignment of StrV-1 to a distinct species of the genus Cytorhabdovirus. Acyrthosiphonmalvae, A.fabae, and A.ruborum were shown to transmit StrV-1 under experimental conditions.
Keywords: vysoce účinné nukleotidové sekvenování; Plant Diseases; Plant Leaves; jahodník; Fragaria; zvířata; Rhabdoviridae; genom virový; High-Throughput Nucleotide Sequencing; Phylogeny; fylogeneze; listy rostlin; mšice; Aphids; Genome, Viral; nemoci rostlin; Animals